Forecasted Climate Analysis from 2000 to 2100 Using RCP 4.5 and RCP 8.5 Model Scenario as A Hazard Early-Warning System in Prague City, Czech Republic - Khoirunisa, Risty (UI Scholars Hub, 2022)
In the last decades, the increasing number of populations in urban areas is dramatically increased. According to the to the 2018 Revision of World Urbanization Prospects more people live in urban areas, around 55 percent of the world’s population in 2018 and are projected into two thirds of global population in 2050. As the world continues to growth, the lands need to be converted thus deforestation happen. If this continues, the greenhouse gas emission will increase and the climate change will become a threat in the future. Therefore, it become essential to understand how the climate will change in the future through model scenario. The study will asses from three aspects of climate, namely, precipitation, near surface air temperature and maximum wind speed in Prague City, the city that was heavily populated and one of popular destinations for tourism. The objectives were to analyse the future climate based on these three aspects and predict what future hazard which might come n the upcoming years. The outcome can be a basis for early-warning system in urban areas. The methods were employed by using Recipient Concentration Pathways (RCP) scenario of 4.5 as stabilization scenario and 8.5 as pessimistic scenario in Regional Model RCA4. The study found that in several years until 2060, Prague will face more urban flooding based on the model scenario RCP 8.5.